ANALISIS DAMPAK MEDIA SOSIAL DI KOTA BANDUNG SEBAGAI KOTA PILIHAN UNTUK BERWISATA - Permana, Agam Julian; Ginting, Ayu Rahayu Muliani; Putri, Nathaya Rasendriya; Zharifa, Shania Siti Nur; Novita, Syalwa; Permana, Zahira Rafeyfa (JURNAL MATA PARIWISATA, 2024)
The tourism sector in Bandung City continues to increase in terms of the development of tourist objects that are increasingly varied and have an impact on other sectors such as the economy, society, and environment. The Ministry of Tourism and Creative Economy of the Republic of Indonesia stated that Bandung was ranked 15th out of 25 cities in the world with the category "Best of The Best Destination Travelers Choice" and entered into the ranks of "World Trending Destinations 2024" by TripAdvisor. Achievements in the tourism sector in Bandung City are inseparable from new trends that continue to innovate to increase interest in travel and the influence of globalization on the delivery of information about tourist destinations can be widespread. The emergence of social media with various variables and different features can have a good impact on the progress of the tourism sector. This study discusses the impact of social media on the choice of tourists to travel to Bandung City. This research uses a quantitative method with a descriptive approach. The data obtained in the study came from distributing questionnaires distributed to respondents through the Google form page. Respondents are tourists from outside the city of Bandung and have travelled to the city of Bandung. The results of the study aim to determine the role of social media in making tourist decisions to travel in Bandung City which will be useful in the development of tourism marketing in Bandung City so that it is increasingly innovative and creative.